Multicomponent Transcriptional Regulation at the Complex Promoter of the Exopolysaccharide I Biosynthetic Operon of Ralstonia solanacearum - Garg, Ram P. (American Society for Microbiology, 2000)
High-level transcription of eps, an operon encoding biosynthesis of an exopolysaccharide virulence factor of the phytopathogen Ralstonia (Pseudomonas) solanacearum, requires the products of at least seven regulatory genes (phcA, phcB, xpsR, vsrA-vsrD, and vsrB-vsrC), which are organized in three converging signal transduction cascades. Because xpsR and the vsrB-vsrC two-component system are the most downstream cascade components required for activation of eps, we explored how these components control transcription from the eps promoter (P(eps)). Deletion and PCR mutagenesis identified an upstream region of P(eps) (nucleotides −82 to −62) that is critical for transcription activation by VsrB-VsrC and XpsR and also is required for negative control of P(eps) by the putative eps regulator EpsR. Using PCR mutagenesis we generated the vsrC1 allele that encodes a response regulator that constitutively activates P(eps) in the absence of its cognate sensor, VsrB. However, activation of P(eps) by vsrC1 still required xpsR. Unexpectedly, the amino acid substitution conferring the constitutive phenotype on VsrC1 is 12 residues from its C terminus, outside the known functional domains of response regulators. Finally, a modified DNase I footprinting method was used to demonstrate specific binding of both VsrC1 and VsrC to the −72 to −62 upstream region of P(eps).